Penerapan Model Student Centered Learning dalam Pembelajaran Musik - Birul Walidaini (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: Learning is a process that involves the teacher and the learning participants. In learning, a model is needed as a reference in carrying out learning. Methods. Methods used include pre-instructional, core learning, and evaluation. This model broadens learners' horizons through active involvement in deep guitar practice. Educators act as facilitators who help students develop musical skills and understanding. Result and Discussion: This paper will describe the application of the student-centred learning model to music learning, specifically in guitar repertoire class, one of the subjects in the music arts education department of FBSB UNY. The characteristic of the student-centred learning model is to place participants or students as the centre of learning and the role of educators as bodyguards and facilitators. At the same time, the stages in its implementation are pre-instructional or planning, the core of learning and evaluation. The results of student-centred learning in guitar repertoire class courses are: (1) the Student-centred Learning model broadens students' horizons, (2) Student-Centered Learning requires the teacher to act as a facilitator in learning practice.